2019
DOI: 10.1167/iovs.18-25698
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on the Role of the Fibrinolytic Pathway on Outflow Facility Regulation

Abstract: PurposeTo understand the role and further dissect pathways downstream of tissue plasminogen activator (tPA) and the fibrinolytic pathway in modulating outflow facility.MethodsOutflow facility of tissue plasminogen activator (Plat) knockout (KO) mice was determined and compared to that of wild-type (WT) littermates. Gene expression of urokinase plasminogen activator (Plau), plasminogen activator inhibitor (Pai-1), plasminogen (Plg), and matrix metalloproteinases (Mmp-2, -9, and -13) was measured in angle tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 50 publications
(73 reference statements)
0
9
0
Order By: Relevance
“…[64][65][66] TGFβ2 also increases PAI-1 expression, which inhibits plasmin activation and thereby negatively regulates activation of MMPs. 15,67 By contrast, inhibition of PAI-1 in TM cells will rescue MMP activity and lower IOP, even while in the presence of elevated levels of TGFβ2. This increase in PAI-1 expression in response to overexpression of active TGFβ2 has also been confirmed in the TGFβ2 ocular hypertensive mouse model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[64][65][66] TGFβ2 also increases PAI-1 expression, which inhibits plasmin activation and thereby negatively regulates activation of MMPs. 15,67 By contrast, inhibition of PAI-1 in TM cells will rescue MMP activity and lower IOP, even while in the presence of elevated levels of TGFβ2. This increase in PAI-1 expression in response to overexpression of active TGFβ2 has also been confirmed in the TGFβ2 ocular hypertensive mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…ID1 is known to suppress PAI-1 and uPA expression and thereby control MMP2, MMP3, MMP9, and MMP14 activities. 29 , 30 , 67 , 69 , 71 In addition, ID1 also suppresses expression of the fibrotic proteins thrombospondin-1, LOX, βV-integrin, inhibin betaA, and FN expression in murine fibroblasts. 48 , 50 Recent reports suggest that ID3 plays a critical role in regulating corneal fibrosis by blocking α-smooth muscle actin expression.…”
Section: Discussionmentioning
confidence: 99%
“…Although outflow facility measurement is not adopted in routine clinical practice, it is an important research tool for revealing the physiological properties of the eye and the different mechanisms of antiglaucoma medications and surgeries. 3 , 4 Electronic Schitøz tonometry 5 and pneumatonography 6 have been used to measure the outflow facility in numerous studies. Outflow facility was calculated from the pressure decay curves, and then the C value was estimated using the Langham's pressure-volume relationship tables and a polynomial fitted to the decay curve.…”
mentioning
confidence: 99%
“…Previous studies have relied on a standard qualitative technique to assess DR lesions within and outside the ETDRS fields. 1 , 2 , 6 , 7 Grading takes into account both number and extent of the lesion being graded within the field. If PPL is assessed to be present in any of the peripheral fields, the eye has been considered to have PPL.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have shown that hemorrhages and microaneurysms (H/Mas) are by far the most frequent lesions in PPL (75–95%) and therefore could be used alone as a surrogate marker for PPL presence and severity. 1 , 2 , 6 , 7 PPLs might also be determined automatically by applying the same principles and definitions as global grading to the automated H/Ma counts. 1 , 2 , 6 , 7 This ability would be particularly important given the increased interest in developing rapid automated H/Ma counting techniques for UWF images and its potential use in clinical trials and research studies.…”
Section: Introductionmentioning
confidence: 99%